Promotion of rapid testing for HIV in primary care (RHIVA2): a cluster-randomised controlled trial. Issue 6 (June 2015) - Leber, Werner; McMullen, Heather; Anderson, Jane; Marlin, Nadine; Santos, Andreia C; Bremner, Stephen; Boomla, Kambiz; Kerry, Sally; Millett, Danna; Mguni, Sifiso; Creighton, Sarah; Figueroa, Jose; et al.
Summary: Background: Many people with HIV are undiagnosed. Early diagnosis saves lives and reduces onward transmission. We assessed whether an education programme promoting rapid HIV testing in general practice would lead to increased and earlier HIV diagnosis. Methods: In this cluster randomised controlled trial in Hackney (London, UK), general practices were randomly assigned (1:1) to offer either opt-out rapid HIV testing to newly registering adults or continue usual care. All practices were invited to take part. Practices were randomised by an independent clinical trials unit statistician with a minimisation program, maintaining allocation concealment. Neither patients nor investigators were masked to treatment allocation. The primary outcome was CD4 count at diagnosis. Secondary outcomes were rate of diagnosis, proportion with CD4 count less than 350 cells per μL, and proportion with CD4 count less than 200 cells per μL. This study is registered withClinicalTrials.gov, number ISRCTN63473710. Findings: 40 of 45 (89%) general practices agreed to participate: 20 were assigned to the intervention group (44 971 newly registered adult patients) and 20 to the control group (38 464 newly registered adult patients), between April 19, 2010, and Aug 31, 2012. Intervention practices diagnosed 32 people with HIV versus 14 in control practices. Mean CD4 count at diagnosis was 356 cells per μL (SD 254) intervention practices versus 270 (SD 257) in control practices (adjusted difference of square root CD4 count 3·1, 95% CI −1·2 to 7·4; p=0·16);); in a pre-planned sensitivity analysis excluding patients diagnosed via antenatal care, the difference was 6·4 (95% CI, 1·2 to 11·6; p=0·017). Rate of HIV diagnosis was 0·30 (95% CI 0·11 to 0·85) per 10 000 patients per year in intervention practices versus 0·07 (0·02 to 0·20) in control practices (adjusted ratio of geometric means 4·51, 95% CI 1·27 to 16·05; p=0·021). 55% of patients in intervention practices versus 73% in control practices had CD4 count less than 350 cells per μL (risk ratio 0·75, 95% CI 0·53 to 1·07). 28% versus 46% had CD4 count less than 200 cells per μL (0·60, 0·32 to 1·13). All patients diagnosed by rapid testing were successfully transferred into specialist care. No adverse events occurred. Interpretation: Promotion of opt-out rapid testing in general practice led to increased rate of diagnosis, and might increase early detection, of HIV. We therefore recommend implementation of HIV screening in general practices in areas with high HIV prevalence. Funding: UK Department of Health, NHS City and Hackney.